2017
DOI: 10.18632/oncotarget.16640
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA ANRIL acts as an oncogene and contributes to paclitaxel resistance of lung adenocarcinoma A549 cells

Abstract: Long non-coding RNAs (lncRNAs) are a family of non-protein-coding RNAs that might affect Lung adenocarcinoma (LAD) chemo-resistance and most of them could be used as biomarkers and therapy targets. However, the potential function of lncRNA ANRIL contributed paclitaxel chemo-resistance in LAD is still unknown. This study aimed to observe the expression of ANRIL in LAD, evaluate its biological role in the resistance of LAD cells to paclitaxel and explore the apoptosis role in the ANRIL associated mechanism. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 26 publications
0
46
0
Order By: Relevance
“…LncRNA ANRIL is overexpressed in LUAD tissues and in A549/PTX cells. ANRIL can inhibit apoptosis and induce taxanes resistance via Bcl-2 upregulation and cleaved PARP downregulation (Xu et al, 2017). LncRNA CCAT1 serves as the molecular sponge of let-7c and further upregulates Bcl-xL, which enhances proliferation, attenuates apoptosis, and promotes chemical resistance in LUAD cells (Chen et al, 2016a).…”
Section: Lncrnas and Nsclc Taxanes Resistancementioning
confidence: 99%
“…LncRNA ANRIL is overexpressed in LUAD tissues and in A549/PTX cells. ANRIL can inhibit apoptosis and induce taxanes resistance via Bcl-2 upregulation and cleaved PARP downregulation (Xu et al, 2017). LncRNA CCAT1 serves as the molecular sponge of let-7c and further upregulates Bcl-xL, which enhances proliferation, attenuates apoptosis, and promotes chemical resistance in LUAD cells (Chen et al, 2016a).…”
Section: Lncrnas and Nsclc Taxanes Resistancementioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are novel members of noncoding RNAs with no or limited protein-coding capacity (9,19,22). Increasing studies have shown that several dysregulated lncRNAs act vital roles in cancer genesis through modulating posttranscriptional regulation or gene transcription (18,32,33,35,41). LncRNAs were proven to involve a large range of cellular processes including cell cycle, development, differentiation, growth, apoptosis, and migration (6,8,12,36).…”
Section: Introductionmentioning
confidence: 99%
“…In ovarian 43 and bladder 44 In HCC, sponging of liver enriched miR-122-5p by ANRIL induces cell proliferation, metastasis and invasion 47 . Interestingly, ANRIL was reported to contribute to paclitaxel resistance in lung cancer, partly through poly(ADP-ribose) polymerase (PARP) and BCL2 modulating mitochondrial pathway 48 .…”
mentioning
confidence: 99%